Two apples a day lower serum cholesterol and improve cardiometabolic biomarkers in mildly hypercholesterolemic adults: a randomized, controlled, crossover trial. Issue 2 (16th December 2019) - Koutsos, Athanasios; Riccadonna, Samantha; Ulaszewska, Maria M; Franceschi, Pietro; Trošt, Kajetan; Galvin, Amanda; Braune, Tanya; Fava, Francesca; Perenzoni, Daniele; Mattivi, Fulvio; Tuohy, Kieran M; Lovegrove, Julie A
ABSTRACT: BACKGROUND: Apples are rich in bioactive polyphenols and fiber. Evidence suggests that consumption of apples or their bioactive components is associated with beneficial effects on lipid metabolism and other markers of cardiovascular disease (CVD). However, adequately powered randomized controlled trials are necessary to confirm these data and explore the mechanisms. OBJECTIVE: We aimed to determine the effects of apple consumption on circulating lipids, vascular function, and other CVD risk markers. METHODS: The trial was a randomized, controlled, crossover, intervention study. Healthy mildly hypercholesterolemic volunteers (23 women, 17 men), with a mean ± SD BMI 25.3 ± 3.7 kg/m 2 and age 51 ± 11 y, consumed 2 apples/d [Renetta Canada, rich in proanthocyanidins (PAs)] or a sugar- and energy-matched apple control beverage (CB) for 8 wk each, separated by a 4-wk washout period. Fasted blood was collected before and after each treatment. Serum lipids, glucose, insulin, bile acids, and endothelial and inflammation biomarkers were measured, in addition to microvascular reactivity, using laser Doppler imaging with iontophoresis, and arterial stiffness, using pulse wave analysis. RESULTS: Whole apple (WA) consumption decreased serum total (WA: 5.89 mmol/L; CB: 6.11 mmol/L; P = 0.006) and LDL cholesterol (WA: 3.72 mmol/L; CB: 3.86 mmol/L; P = 0.031), triacylglycerol (WA: 1.17 mmol/L; CB: 1.30 mmol/L; P = 0.021), and intercellular cell adhesion molecule-1 (WA: 153.9 ng/mL; CB: 159.4 ng/mL; P = 0.028), and increased serum uric acid (WA: 341.4 μmol/L; CB: 330 μmol/L; P = 0.020) compared with the CB. The response to endothelium-dependent microvascular vasodilation was greater after the apples [WA: 853 perfusion units (PU), CB: 760 PU; P = 0.037] than after the CB. Apples had no effect on blood pressure or other CVD markers. Conclusions: These data support beneficial hypocholesterolemic and vascular effects of the daily consumption of PA-rich apples by mildly hypercholesterolemic individuals. This trial was registered at clinicaltrials.gov as NCT01988389.